Numerical Study of the Reed Valve Impact in the Rotary Compressor by FSI Model. (May 2017) - Yu, Xiaoling; Tan, Qin; Ren, Yumei; Jia, Xiaofei; Jin, Liwen
Abstract: The reed valve impact is the main reason leads to the valve fatigue failure, the valve noise and energy consumption of the rotary compressor. This paper built up a three dimensional fluid-structure interaction (FSI) model of the dynamic behaviour of the reed valve in a rotary compressor with the rotational speed of 4800 rpm. Then the P-θ diagram inner the cylinder was tested in an experiment to validate the FSI model. By the FSI model, the impact process, the impact stress and the impact velocity respectively for the reed impact against the retainer and the seat were investigated. It was found that for the reed impact against the retainer, the impact occurred at some local spots moving from the neck to the outer edge of the reed head in sequence rather than at all spots on the whole reed head simultaneously. The whole impact process finishes within the rotation angle of 1 o . The highest impact velocity as well as the highest impact stress happens at the outer edge of the reed head. The research results are helpful to the design and failure diagnosis of the reed valve, as well as to energy saving of the rotary compressor.